EFEKTIFITAS METODE MIND MAPPING UNTUK MENINGKATKAN PRESTASI BELAJAR FISIKA PADA SISWA KELAS VIII - Chomsi Imaduddin, Muhammad; Haryanto Nur Utomo, Unggul (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
This study aimed to determine the effectiveness of mind mappingmethod to improve the learning achievements of physics. The subjects ofthis study were students in grade VIII of SMP Muhammadiyah 8 Yogyakartawhich have average score of physics subjects below 6.5, and have theability to see and hear well. Data collection methods used in this study wasthe academic score on the physics subject of optical tools, documentation,observation and interview. This study used the experimental method ofpretest-posttest with control group design and used the t-test analysis.The results of paired sample t-test analysis in experimental group obtainedthat mind mapping method has highly significant positive effect in enhancingachievement of physics learning (t = -11.006, p = 0.000). The results ofthe paired sample t-test analysis in control group showed that conventionalmethod has insignificant influence on achievement enhancement of physicslearning (t = -1.941, p = 0.070) and the independent sample t-test in bothgroup found that there are significant difference of average (mean) posttestscore between the experimental group and control group (t = 2.144, p =0.020). The results demonstrate mind mapping method is very effective inimproving the learning achievements of physics.